Cog in the wheel: Resource release and the scope of interdependencies in corporate adjustment activities - Keum, Dongil D. (Strategic Management Journal, 2020)
Abstract Research Summary This study characterizes and tests interdependencies in corporate activities used to adjust resources and implement change. Because each activity contributes only a partial result and depends on others to complete an intended change, constraining one can create a bottleneck that traps multiple other activities. For my empirical analysis, I leverage the staggered adoptions of employment protection laws intended to constrain one specific adjustment to one specific resource: dismissing employees. The constraint, however, not only affects the contraction but also the expansion in labor as well as capital investments, acquisition, divestiture, CEO turnover, and other adjustments, and increases (shortens) the persistence of negative (positive) performance. The expansive interdependencies are critical to understanding firm rigidity and resilience, implementation failures, and the persistence of firm performance. Managerial Summary This study shows how executing even a seemingly straightforward improvement requires piecing together a series of interdependent corporate strategic activities. As a result, a constraint on just one is sufficient to foil a successful firm response. Using changes in employment laws, I show that a firm's ability to dismiss employees not only affects firing, but also hiring, capital investments, acquisition, divestiture, and CEO turnover, and increases (shortens) the persistence of negative (positive) performance. Underestimating the complex and interdependent nature of these activities can lead to bias‐for‐action and contribute to implementation failures, such as cost overruns, schedule delays, and a post‐merger integration process that fails to realize expected synergies.